Gambus Hadhramaut: The Malaysian malay lute tuning retrieval - Hamdan, Sinin; Mohamad Said, Khairul Anwar; Rahman, Md Rezaur; Sawawi, Marini; Sinin, Aaliyawani Ezzerin (BioResources, 2023)
This study identified elements in a simple homemade gambus from a local crafter using a scientific approach. The gambus was made from geronggang wood (Cratoxylum arborescens), a light Malaysian hardwood with pink sapwood, distinct from the heartwood with brick-red or deep pink. The sound was processed to generate fast Fourier transform (FFT) and time-frequency analysis (TFA) using PicoScope and Adobe Audition software, respectively. The gambus A 1st string (note C4#) displayed a harmonic overtone at the 1st and 2nd octave. The 2nd string (note A3) showed harmonic overtone at the 1st, 2nd, and 3rd octave. The 3rd string (note D3#) showed a significant fundamental peak and harmonic overtone at the 1st, 2nd, 3rd, 4th, and 5th octave. The 4th string (note A2#) displayed consistent harmonic overtones at the 1st, 2nd, 3rd, 4th, and 5th octave. The 5th string (note E2) had a harmonic overtone at the 5th octave. Gambus A showed an inconsistent signal in the 6th string (note D2#) with inharmonic overtone at 3.35th and 6.79th overtones. The gambus A 1st to 6th strings are C4#, A3, D3#, A2#, E2, and D2#, respectively. The gambus B 1st to 6th strings are C4, G3, D3, A3, E3, and B2, respectively.